assume $X,\ Y$ are two independent random variables

$X \sim \mathrm{Poisson}(a)$


$Y \sim \mathrm{Exponential}(\frac1{a})$

find out $P(X < Y)$

Thank you!


We solve a marginally more general problem. Let $X$ be Poisson with parameter $\lambda$. Let $Y$ be exponential with parameter $\tau$. By this we mean that $Y$ has density function $\tau e^{-\tau y}$. Given that $X$ and $Y$ are independent, we find the probability that $X\lt Y$.

Given that $X=k$, the probability that $Y\gt X$ is $e^{-k \tau}$. This is because in general, $\Pr(Y\gt y)=e^{-\tau y}$. But the probability that $X=k$ is $e^{-\lambda}\frac{\lambda^k}{k!}$.

Thus the probability that $X=k$ and $Y\gt X$ is equal to $e^{-\lambda}\frac{\lambda^k}{k!}e^{-k\tau}$. For the probability that $X\lt Y$, add up over all $k$. Our required probability is therefore equal to $$\sum_{k=0}^\infty e^{-\lambda}\frac{\lambda^k}{k!}e^{-k\tau}.$$

This is a correct answer, but it can be greatly simplified. Note that $$\lambda^ke^{-k\tau}=(\lambda e^{-\tau})^k.$$ So our answer is $$e^{-\lambda}\sum_{k=0}^\infty \frac{b^k}{k!},$$ where $b=\lambda e^{-\tau}$. But we recognize the sum as just $e^b$. So the required probability can be written as $$e^{-\lambda}e^{\lambda e^{-\tau}}\quad\text{or equivalently}\quad e^{-\lambda(1-e^{-\tau})}.$$

  • 1
    $\begingroup$ ok, thank you very much! I understand your method, but I think there might be a slight error. Y ~ Exp(1/a), not Exp(a); so given X = k, probability that Y > X is e^(-k/a). $\endgroup$ – Ionut Laceanu Jan 29 '13 at 14:01
  • $\begingroup$ Thank you. Actually the same argument works for Poisson parameter $c$, exponential parameter $d$. Maybe I'll change the writeup to that. Everybody mean by Poisson($\lambda$) that $\lambda$ is the mean. But there are two usages for Exp($c$)$. The $c$ can be the mean, or it can be the reciprocal of the mean. Which is it in your course? $\endgroup$ – André Nicolas Jan 29 '13 at 16:33
  • $\begingroup$ In my course, if X~Exp(c), then E(X), or the expected value / mean equals 1/c, because the density is c*e^(-c). so I guess that c is the reciprocal of the mean. Thank you again for your answer. $\endgroup$ – Ionut Laceanu Jan 29 '13 at 21:53
  • $\begingroup$ You are welcome. In my revised answer, with the $\lambda$ and $\tau$, we have $\lambda=a$, $\tau=1/a$, just like you observed in your first comment. The $a$ and $1/a$ do not combine in any interesting way in the formula we get. $\endgroup$ – André Nicolas Jan 29 '13 at 22:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.